The European Court of Auditors as an audit institution. - Anna Wójtowicz-Dawid (Journal of Modern Science, 2024)
Objectives The main objective of the publication is to analyse the significance and role of the European Court of Auditors in the system of management and control of the spending of funds from the European Union budget. The basic thesis of the publication is that the European Court of Auditors is an audit institution and functions within an audit system. Furthermore, the positioning of the European Court of Auditors among audit institutions brings with it a different perception of the institution. The descriptive aim of the publication is to show the link between the ECA as an audit institution and the trust it enjoys, and to analyse whether, by functioning as an audit institution, it has a greater influence on the proper spending of public funds from the EU budget then by being a control institution.